2013
DOI: 10.1007/s11916-013-0332-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trigeminal Microvascular Decompression in the Treatment of SUNCT and SUNA

Abstract: Short-lasting unilateral neuralgiform headache with conjunctival injection and tearing (SUNCT) and short-lasting unilateral neuralgiform headache attacks with cranial autonomic symptoms (SUNA) are primary headache disorders. Evidence suggests that SUNCT/SUNA have similar pathophysiology to the trigeminal autonomic cephalalgias and involves the trigeminal autonomic reflex. This review provides an overview of microvascular decompression of the trigeminal nerve and other surgical therapeutic options for SUNCT/SUN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…Unfortunately, given the rarity of short lasting unilateral neuralgiform headache attacks it seems unlikely that high quality, properly powered randomised control trials of VTA-DBS will ever be performed. Microvascular decompression, occipital nerve stimulation and deep brain stimulation have all been found to be effective in open-label series with response rates of over 75% (Leone et al, 2005, Bartsch et al, 2011, Sebastian et al, 2013, Lambru et al, 2014. The invasiveness of surgery, associated risks, the need for implanted hardware and the cost of treatment will all influence individual patient options.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, given the rarity of short lasting unilateral neuralgiform headache attacks it seems unlikely that high quality, properly powered randomised control trials of VTA-DBS will ever be performed. Microvascular decompression, occipital nerve stimulation and deep brain stimulation have all been found to be effective in open-label series with response rates of over 75% (Leone et al, 2005, Bartsch et al, 2011, Sebastian et al, 2013, Lambru et al, 2014. The invasiveness of surgery, associated risks, the need for implanted hardware and the cost of treatment will all influence individual patient options.…”
Section: Discussionmentioning
confidence: 99%
“…10 In SUNCT patients who underwent microvascular decompression, 12 of 19 patients (63%) had a good outcome at 14 months. 28 It has been suggested that there is dual pathophysiology in SUN, firstly the activity of the posterior hypothalamus which causes central disinhibition of the trigemino-autonomic reflex, similar to the other TACs, and also an area of focal demyelination of the trigeminal sensory root due to vascular compression near the root entry zone, thus generating spontaneous ectopic impulses which cause short-lasting spontaneous attacks and allow triggers by cutaneous stimuli. 29 The suggestion of dual pathology is borne out by a case report of a patient with SUNCT who had bilateral hypothalamic activation in functional imaging, and who became pain free after microvascular decompression on the side ipsilateral to his symptoms.…”
Section: Sunct Suna and Trigeminal Neuralgiamentioning
confidence: 99%
“…There is a growing literature of patients with SUN who have neurovascular conflict with the trigeminal nerve, in up to 90% of cases . In SUNCT patients who underwent microvascular decompression, 12 of 19 patients (63%) had a good outcome at 14 months …”
Section: Introductionmentioning
confidence: 99%
“…After a 14-month follow-up, 63 % had complete resolution of pain and the rest had little or no change. Adverse effects included wound infection, vertigo, and jaw pain, and more serious effects of persistent hearing loss and ataxia [82••]. Larger patient numbers and follow-up periods are needed, but MVD appears a sensible option in refractory patients with an aberrant vessel on imaging before attempting neuromodulation, which is more expensive and invasive.…”
Section: Short-lasting Unilateral Neuralgiform Headache Attacksmentioning
confidence: 99%